Replacing dichloroethane as a solvent for rhodium-catalysed intermolecular alkyne hydroacylation reactions: the utility of propylene carbonate - Lenden, P; Ylioja, P; Gonzalez-Rodriguez, C; Entwistle, D; Willis, M (2011)
Propylene carbonate is an excellent solvent for rhodium-catalysed intermolecular alkyne hydroacylation reactions, allowing a variety of β-S-aldehydes and alkynes to be combined in high yields, to deliver enone products. The effective use of propylene carbonate removes the need to employ dichloroethane as solvent. © 2011 The Royal Society of Chemistry.